2015
DOI: 10.1515/biolog-2015-0108
|View full text |Cite
|
Sign up to set email alerts
|

The parasite community of gobiid fishes (Actinopterygii: Gobiidae) from the Lower Volga River region

Abstract: The parasitic fauna in the lower Volga River basin was investigated for four gobiid species: the nonindigenous monkey goby Neogobius fluviatilis (Pallas, 1814), the round goby N. melanostomus (Pallas, 1814), the Caspian bighead goby Ponticola gorlap (Iljin, 1949), and the tubenose goby Proterorhinus cf. semipellucidus (Kessler, 1877). In total, 19 species of goby parasites were identified, of which two - Bothriocephalus opsariichthydis Yamaguti, 1934 and Nicolla skrjabini (Iwanitzki, 1928) - appeared to have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Although occurring sympatrically with infected fishes, gobioid fishes were often not infested by L. cyprinacea (e.g. Kritscher, 1975;Kvach, 2004;Dalu et al, 2012;Krasnovyd et al, 2012;Kvach et al, 2014Kvach et al, , 2015Zhokhov et al, 2017) (Tab. S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although occurring sympatrically with infected fishes, gobioid fishes were often not infested by L. cyprinacea (e.g. Kritscher, 1975;Kvach, 2004;Dalu et al, 2012;Krasnovyd et al, 2012;Kvach et al, 2014Kvach et al, , 2015Zhokhov et al, 2017) (Tab. S1).…”
Section: Discussionmentioning
confidence: 99%
“…Especially Gobioidei, a clade of fishes adapted primarily to a benthic life style, are rarely infected by L. cyprinacea (e.g. Kvach, 2004;Nagasawa et al, 2007;Kvach et al, 2015;Zhokhov et al, 2017). All records to date of infested Gobioidei were from Asia and from the Ponto-Caspian region (Tab.…”
Section: Introductionmentioning
confidence: 99%
“…The taxon is considered monophyletic representing an ancient digenean lineage ( Achatz et al, 2019 ). The presence of cyathocotylid metacercarie in various freshwater fishes was documented in Czechia ( Kvach et al, 2016 ), Finland ( Näreaho et al, 2017 ), France ( Gettová et al, 2016 ), Slovakia ( Ondračková et al, 2009 ) and Russia ( Kvach et al, 2015 ). Human infections have not been documented but mammals (dogs) have been suggested as potential hosts of adult cyathocotylids ( Chandler, 1950 ; El-Assal et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tapeworm Ligula pavlovskii Dubinina 1959 occurs primarily in the Ponto-Caspian gobiids, and has been recorded from only a few fish species from the Ponto-Caspian region, specifically stellate tadpole-goby (Benthophillus stellatus), monkey goby (Neogobius fluviatilis), round goby, bighead goby (Ponticola kessleri), syrman goby (Ponticola syrman), marbled goby (Pomatoschistus marmoratus), and an unclear species from genus Knipowitschia (Yuryshynets et al, 2017). Although plerocercoids are large bodied parasites (Fig 1 .), to our knowledge no study to date has reported their occurrence in non-native populations of Ponto-Caspian gobies (Kudrenko and Kvach, 2005;Kvach et al, 2015Kvach et al, , 2014Kvach and Stepien, 2008;Mierzejewska et al, 2014; Appendix A) except a single specimen from Ros river, near Kiev (Kvach and Ondračková, 2020;Zaichenko, 2015) that was found in a sample of 288 monkey goby individuals.…”
Section: Introductionmentioning
confidence: 99%